Pemanfaatan Media Sosial Instagram Dalam Membangun Brand Image Pada Klub Internal Persebaya Amatir - Idris Ariyanto; Supriyono Supriyono (Pakis Journal Institute, 2024)
This research provides in-depth insight into optimizing the use of Instagram as an effective branding tool, with an emphasis on high-quality visual content to maintain brand consistency that is able to stimulate more active consumer interaction. As a football club, Persebaya Amateur feels the need to expand its reach and interaction with its audience, especially through social media as the main communication channel. The main focus of this research is on the Instagram platform, which is the main media used by the club. To obtain accurate data and information, careful research methods are used. The findings from this research can provide a deeper insight into the club, especially within the internal scope of Persebaya Amateur, to understand consumer behavior on social media and design branding strategies that are more targeted. This strategy involves consistent branding activities, focuses on the club's identity values, and can increase audience interaction and engagement. Practically, the results of this research can guide amateur football clubs and similar organizations in designing more effective branding strategies through social media, with the aim of increasing audience interaction and involvement, as well as strengthening the club's identity and image.